Pengaruh Penggunaan LKPD dengan Teknik SCAMPER terhadap Hasil Belajar Kelas IV di Sekolah Dasar Negeri 4 Palembang - Dwi Sagita, Silvia (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2019)
This study aimed to determine the effect of using worksheet in SCAMPER method on learning outcomes of fourth graders at Public Elementary School Number 4 Palembang (Sekolah Dasar Negeri). This study was the Pre-Experimental Design with the type one group pretest-posttest design. The sample of study consisted amounted to 29 fourth graders. The instrument were a 20 items multiple choise written tes and 10 item questionnaire. Data analysis this study used t-test formula, comparing pretest and posttest obtained score. The effect of the SCAMPER-based worksheet method seen from the average posttest was 67.5 pretest and posttest data and normal distribution with a value of 0.66 and -0.20 km. Because tcount> ttable then Ho is rejected and Ha was accepted. So it could be concluded that there is an effect of using SCAMPER-based worksheet on learning outcomes.Key words: SCAMPER tekcnik, LKPD, Learning Outcomes